The urgency of recovering state financial losses based on Law Number 31 of 1999 amendments to Law Number 20 of 2001 concerning the eradication of corruption crimes in Indonesia - Pauzi Muhammad; Piet Yardi (Journal of Social, Humanity, and Education, 2025)
Purpose: This study aims to analyze the urgency of recovering state financial losses caused by corruption, as regulated in the relevant anti-corruption laws, and to explore the potential for incorporating restorative justice into the Indonesian anti-corruption legal framework. Research methodology: The study employs a normative legal research method, using statutory and case approaches. It analyzes relevant laws, judicial decisions, and international conventions such as UNCAC, to evaluate mechanisms for recovering state losses and propose policy improvements.. Results: The study finds that the return of state financial losses does not eliminate criminal liability for corruption offenders under Indonesian law. However, such restitution may serve as a mitigating factor in sentencing. It also identifies weaknesses in the civil recovery process and emphasizes the inefficiency of current mechanisms. The research supports the inclusion of restorative justice to enhance efficiency and effectiveness in asset recovery. Conclusions: The existing legal framework prioritizes retributive justice, which often delays the recovery of losses. A paradigm shift toward restorative justice, especially in corporate corruption cases, can support state financial recovery without necessarily eliminating criminal sanctions. Limitations: This study focuses solely on corruption cases involving state financial losses and does not fully address systemic reform needs. The civil law procedures discussed remain constrained by conventional legal frameworks. Contribution: This research contributes to legal scholarship by proposing a reformulation of corruption law enforcement through restorative justice principles. It informs policy makers and legal practitioners on the potential integration of non-punitive measures in corruption cases and supports the development of a comprehensive legal system for recovering state assets in line with international norms.